The shaping of narrative in Polybius - Miltsios, Nikos, 1980- (Trends in classics. Supplementary volumes ;, 2013)
In his attempt to explain Rome's rise to world power, Polybius composed a carefully structured narrative. Yet, despite its sophistication, Polybius' narrative artistry has received little scholarly attention. This study is the first book-length narratological analysis of the Histories. It contributes to our understanding of its content and purpose by unveiling the narrative strategies employed by Polybius in shaping his intriguing story.